2022
DOI: 10.1108/ccsm-12-2021-0228
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impacts of microlevel CSR activities on firm sustainability: mediating role of CSR performance and moderating role of top management support

Abstract: PurposeThe purpose of this study is to investigate the impacts of microlevel corporate social responsibility (CSR) activities on firm sustainability. The study also examines the mediating roles of CSR performance (CSRP) and top management support on firm sustainability.Design/methodology/approachWith the help of existing literature and theories, a theoretical model has been developed, which is then validated using structural equation modeling technique considering 327 respondents who perform CSR activities at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 80 publications
(129 reference statements)
1
17
0
Order By: Relevance
“…The results proved that Italy and Greece had the highest number of certificates, meaning that companies had high interest in and concern regarding their workplaces, employees, and leadership styles. Moreover, our results align with the study of Chatterjee et al (2022), who agree that top and middle management support and decision‐making are crucial for the implementation of CSR and exert a positive impact on the sustainability and CSR performance of businesses. Corporate responsibility needs to be the principal value for interactions within an organization; only then is it possible to broaden CSR and exert a societal impact.…”
Section: Discussionsupporting
confidence: 91%
“…The results proved that Italy and Greece had the highest number of certificates, meaning that companies had high interest in and concern regarding their workplaces, employees, and leadership styles. Moreover, our results align with the study of Chatterjee et al (2022), who agree that top and middle management support and decision‐making are crucial for the implementation of CSR and exert a positive impact on the sustainability and CSR performance of businesses. Corporate responsibility needs to be the principal value for interactions within an organization; only then is it possible to broaden CSR and exert a societal impact.…”
Section: Discussionsupporting
confidence: 91%
“…The penultimate paper is titled "Investigating the impacts of microlevel CSR activities on firm sustainability: mediating role of CSR performance and moderating role of top management support" in the Indian context. In this study, Chatterjee et al (2023) found that micro-level CSR activities impact enterprise CSR performance under the moderating influence of top management support.…”
mentioning
confidence: 81%
“…Patients who are content with the health-care services they receive are more likely to revisit the same hospital or physician, thereby fostering a mutually beneficial relationship between patients and health-care providers. In such circumstances, patients are significantly more inclined to adhere diligently to their treatment and foster enduring, relationships with their physicians, reducing the likelihood of action against health-care providers (Chaudhuri et al , 2022; Srinivasulu, 2022; Vrontis, 2022; Wang et al , 2023). This, in turn, facilitates collaboration between patients and health-care providers.…”
Section: Theoretical Modellingmentioning
confidence: 99%